BRDF-dependent accuracy of array-projection-based 3D sensors - Heist, Stefan; Kuehmstedt, Peter; Tuennermann, Andreas; Notni, Gunther (Applied Optics, 2017)
In order to perform high-speed three-dimensional (3D) shape measurements with structured light systems, high-speed projectors are required. One possibility is an array projector, which allows pattern projection at several tens of kilohertz by switching on and off the LEDs of various slide projectors. The different projection centers require a separate analysis, as the intensity received by the cameras depends on the projection direction and the object's bidirectional reflectance distribution function (BRDF). In this contribution, we investigate the BRDF-dependent errors of array-projection-based 3D sensors and propose an error compensation process.
CRIS-Team Scopus Importer:2023-04-20